Pendidikan Islam Perspektif Ibnu Khaldun - Sirajudin, Sirajudin; Khojir, Khojir; Soe’oed, Rahmat (JURNAL ILMU PENDIDIKAN & SOSIAL (SINOVA), 2023)
This research aims to analyze education from Ibnu Khaldun's perspective, including biography, concepts, goals, curriculum, and methods. This research was carried out using a qualitative approach using a type of literature study by exploring various works and writings of Ibnu Khaldun related to education. The result of this research is that Ibnu Khaldun believes that education is the core of human existence. True humanity can be realized through the educational process as a result of self-development, considering that humans naturally develop their potential to fulfil their life needs. In the context of the curriculum, Ibnu Khaldun explains the curriculum as an educational program that involves objectives, content, teaching methods, and learning assessment. In his view, Ibnu Khaldun groups knowledge into three categories. First, the group of oral sciences such as naf science, bayan science, and literary science. Ibnu Khaldun emphasized the importance of creative teaching methods to obtain positive student responses while warning against using violent tactics because they can form negative character traits. Ibnu Khaldun suggested that the teachings of the Koran should be emphasized as soon as students reach the level of thinking ability because the Koran can strengthen faith in God and guide good behaviour as servants of God.